One-Pot Synthesis of 7-N,N-dimethylamino-2-naphthol Using 2,7-Dihydroxynaphthalene: A Highly Selective Bucherer Reaction - Wen, N.; Peng, X.; Liu, M.; Ma, Y.; Bai, Ruoyu (Asian Journal of Chemistry, 2013)
This work provides an efficient process for producing 7-N,N-dimethylamino-2-naphthol, which can be selectively prepared by one-pot amination of 2,7-dihydroxynaphthalene by employing the molar ratio of 1 : 1.1 : 1.07 of 2,7-dihydroxynaphthalene: sodium bisulfite : dimethylamine at 60 ºC during 2.5 h.